Myths, Beliefs and Realities: Public-Private Competition and Program Diversification in Higher Education. - Teixeira, Pedro (2016)
In recent years we have observed significant growth in the private sector in many higher education systems around the globe. This growth of private higher education is associated with high political expectations, notably concerning greater choice of programs and greater responsiveness of institutions to students’ and labor market’s demands. Looking at the experience of several European and Latin American countries, this study analyzes the patterns of program diversification of public and private higher education and discusses the impact of the private sector for the diversification of higher education’s supply. The results show a contrasting picture between political beliefs about privatization in higher education and its actual results, suggesting that private institutions tend to be far more specialized than their public counterparts.